Progress of the Soviet Union and Ukrainian scouting-research and fishing activities on the Kerguelen Plateau: impact and consequences ... - Pshenichnov, Leonid (Cybium, 2011)
The first Soviet fishing research began in 1967 on the Kerguelen Plateau. This research expansion in the Indian sector of the Southern Ocean is associated with achievements in whaling and the discovery of many large fishes and squids in the stomachs of toothed whales. This suggested that the area supported high bioproductivity and possible substantial fish stocks. In 1970 and 1971, more than 3 000 t and 200 000 t respectively, were caught, where more than 70% of catch are Marbled notothenia (Notothenia rossii). Thirty large-capacity trawlers operated in the area at that time. In 1974, fishing was based on Mackerel icefish (Champsocephalus gunnari). In 1977, fishing expanded on some rises and banks around the main Kerguelen shelf. This expansion was because of scouting-research vessels taking part in fishing expedition. In 1984, aggregations of Patagonian toothfish (Dissostichus eleginoides) were found and fished with bottom trawls. Data systematization in the 1970s permitted regular (annual) stock ...